Pengaruh Turnover Intentions, Burnout, Dan Work-Life Balance Terhadap Kinerja Karyawan Di Koperasi Simpan Pinjam Primkoppabri (Primer Koperasi Purnawirawan Abri) Kabupaten Blitar - Verdy Febrian Cahyo Utomo; Afi Racmat Slamet; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research was conducted at the PRIMKOPPABRI Savings and Loan Cooperative (Primer Koperasi Purnawirawan ABRI) Blitar District. The purpose of this study was to examine and analyze the effect of Turnover Intentions, Burnout, and Work-Life Balance on the Performance of Employees of the PRIMKOPPABRI Savings and Loan Cooperative (Primer Koperasi Purnawirawan ABRI) in Blitar Regency. The method used to determine sampal is saturated sample, so the total sample used is 53 employees. Data collection methods by collecting primary and secondary data. Hypothesis testing and coefficient of determination tests using multiple regression analysis using SPSS 16.0 for Windows software.The results showed that there was a simultaneous influence of the variables Turnover Intentions, Burnout and Work-Life Balance on Employee Performance. In addition, the Turnover Intentions variable has a partially significant effect on the performance of employees of the PRIMKOPPABRI Cooperative Savings and Loans (Primer Koperasi Purnawirawan ABRI), while the Burnout and Work-Life Balance variables do not have a significant effect partially on the performance of employees of the Savings and Loan Cooperative of PRIMKOPPABRI (Primer Koperasi Purnawirawan ABRI)Blitar Regency, while the Burnout and Work-Life Balance variables do not have a significant effect partially on the performance of employees ) Blitar Regency. Keywords: Turnover Intentions, Burnout, Work-Life Balance, and Employee Performance.